URETERAL EXTRACORPOREAL SHOCK-WAVE LITHOTRIPSY UTILIZING DORNIER MFL-5000 - (:unkn) unknown (MARY ANN LIEBERT INC PUBL, 1994)
Early reports indicated that stones in the upper ureter that have been manipulated back into the kidney have a higher success rate with SWL than those treated in situ. Difficulties in detecting stones in the mid and lower ureter with lithotripters using ultrasonographic localization also limit in situ SWL of ureteral calculi. We treated 254 patients with ureteral calculi (85 upper, 72 mid, and 97 lower) using in situ SWL on the Dornier MFL 5000. The mean stone volume was 1.4 cm2. Approximately one third of the patients required more than one session. The mean number of shock waves was 2010 (range 1400-3000) with a mean voltage of 20 kV (range 14-30 kV). Fragmentation was achieved in 92.6% of the patients. Only 0.4% of the sessions involved general anesthesia. At 3-month follow-up, available in 75% of the patients, the stone-free rate was 82.6%. Ureteral calculi can be treated effectively in situ by means of SWL.
Keywords: CALCULI; STONES; MANAGEMENT